Analysing corporate governance and accountability practices from an African neo-patrimonialism perspective: Insights from Kenya. (July 2021) - Kimani, Danson; Ullah, Subhan; Kodwani, Devendra; Akhtar, Pervaiz
Highlights: We critically examine corporate governance and accountability practices in Kenya. We investigate how corporate sector reforms are constrained by neo-patrimonialism. Data includes 29 semi-structured interviews, field observations and documents. Neo-patrimonialism influences director appointments and board composition. Neo-patrimonial systems supplant formal institutions leaving them as facades. Abstract: This paper examines corporate governance (CG) and corporate accountability practices in the African context, by focusing on the case of Kenya. Our data comprises a combination of 29 semi-structured interviews, field observations and archival evidence. We reveal how western-originated CG and accountability reforms are constrained or subverted by a vigorous neo-patrimonial regime. The Kenyan corporate sector has well defined legal-rational structures, including an elaborate corporate sector regulatory framework, professionals (i.e. accountants and auditors) and corporate boards. In contrast, however, informal networks and patronage interfere with the nomination and work of non-executive board members, thereby hindering the possibility of an independent monitoring of executive management. A conflictual and inadequately resourced regulatory framework plays a more symbolic than an effective regulative role in enforcing CG and accountability practices. We also find a widespread rent-seeking culture that significantly hinders the exercise of corporate accountability. Furthermore, external auditor independence is problematic due to conflicts of interest and the auditors' dependence on advisory fees, thereby favouring a clientelist association with auditee firms. Overall, our findings reveal that CG and accountability practices, while ostensibly present in Kenya, are largely ineffective due to the influence of neo-patrimonial realities on the mind-set and actions of corporate actors.